Case studies on the implementation of TQM in the Indian leather SMEs. (2016) - Faisal, A. Mohammed
Globalisation has provided an opportunity for small and medium-sized enterprises (SMEs) to create niche markets for themselves, provided they survive the open competition that goes along with it. Leather SMEs (LSMEs) have progressively improved their competitiveness by adopting total quality management (TQM). This resulted in productivity improvement but unable to implement successfully at shop floor level. The objective is to identify the critical success factors (CSFs) of TQM implementation at shop floor level in Indian LSMEs. Two case studies were conducted using replication logic to predict similar and/or contradicting productivity improvements. Analysis of the cases led to the identification of CSFs at shop floor level.